Fallow deer in southern Africa: a potential meat source or is it just an invasive species? - Hoffman, Louw, author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
Where Fallow deer (Dama spp.) were once almost extinct, they have now become one of the most widespread wild ungulate species in the world. In South Africa, this species has also been introduced and is now abundant in the country and could contribute to food security within Africa. However, conservation authorities tend to view this ungulate species as an invasive species whilst game farmers see it as a valuable contributor to farm income: as a hunted trophy or as a source of quality and nutritious meat. Surprisingly, very little is known about its production potential and meat quality in South Africa. Fallow deer have been farmed successfully innumerous countries with the industry in New Zealand being the most prominent. All indication are that this species has adapted well to South African conditions and are highly productive. The meat yield and quality of this species is of the highest standard when adequate harvesting procedures are followed. The fatty acid profile of this species is also beneficial for human consumption. However, antidotal information has it that the meat from stags during the rut has a taint to it: the cause of this has not yet been quantified. Initial results (to be discussed) indicate that the meat quality of this species is of the highest standard typical of wild game animals. However, the distribution of this species needs to be quantified so that strategies can be developed to develop its potential as a sustainable protein source fit for human consumption. The ecological impact of this species also needs to be quantified so that, if required, adequate legislation can be developed to either curb or grow the potential deer farming industry.
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.